2009
DOI: 10.1007/978-3-642-04208-9_49
|View full text |Cite
|
Sign up to set email alerts
|

Error Resilient Speech Coding Using Sub-band Hilbert Envelopes

Abstract: Abstract. Frequency Domain Linear Prediction (FDLP) represents a technique for auto-regressive modelling of Hilbert envelopes of a signal. In this paper, we propose a speech coding technique that uses FDLP in Quadrature Mirror Filter (QMF) sub-bands of short segments of the speech signal (25 ms). Line Spectral Frequency parameters related to autoregressive models and the spectral components of the residual signals are transmitted. For simulating the effects of lossy transmission channels, bit-packets are dropp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The drop-out of bit-packets in the proposed codec corresponds to loss of sub-band signals at the decoder. In [47], it has been shown that the degraded sub-band signals can be efficiently recovered from the adjacent sub-bands in time-frequency plane which are unaffected by the channel.…”
Section: Discussionmentioning
confidence: 99%
“…The drop-out of bit-packets in the proposed codec corresponds to loss of sub-band signals at the decoder. In [47], it has been shown that the degraded sub-band signals can be efficiently recovered from the adjacent sub-bands in time-frequency plane which are unaffected by the channel.…”
Section: Discussionmentioning
confidence: 99%